The distinction between Persuasion and Rhetoric in Plato’s Gorgias - Santos, Claudiano Avelino dos (2012)
Philosophy first developed in a time when the ability to persuade was considered essential for those who wanted to succeed in the polis, hence the prestigious place rhetoric achieved among the Athenians. Plato, however, in the dialogue Gorgias criticizes this activity. But in criticizing it, he does not condemn persuasion, which he regards as fundamental to education.